(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2025)
Animal welfare is a critical aspect of livestock management, yet its implementation among smallholder farmers often remains inadequate. This study assessed the knowledge, attitudes, and practices (KAP) of cattle farmers in Tamangapa Subdistrict, Manggala District, Makassar City, Indonesia, where cattle are grazed at the Tamangapa urban landfill. A structured questionnaire was administered to 32 respondents, and data were analyzed using Spearman correlation, Kruskal-Wallis, and Mann-Whitney-Wilcoxon tests. Results revealed an average knowledge score of 0.92 (out of 1), an attitude score of 4.59 (out of 5), and a practice score of 3.07 (out of 5). No significant correlations were observed between knowledge, attitudes, and practices. However, significant positive correlations were observed between knowledge and the number of cattle (ρ = 0.548; p = 0.001) and between attitude and education (ρ = 0.362; p = 0.042), and a negative correlation between attitude and age (ρ = −0.468; p = 0.007). These results highlight the influence of demographic factors on animal welfare awareness and behaviors, emphasizing the need for targeted education and training programs to bridge the gap between knowledge and practice.